Novel gamma ray spectral analysis for logging-while-drilling - Hooshyari Far, I.; Kepic, Anton; Carson, M. (2016)
Gamma-ray logging is not well appreciated in the mining industry due to the challenge of collecting high quality spectral information. Hence spectrum analysis is not well-developed in this area as well. We have developed a new logging while drilling approach which will allow a borehole to be logged without the necessity of either deploying wireline tools or employing the use of a radioactive source. The slow progress of the drill bit in diamond core drilling allows sufficient time for a suitable detector to accumulate a useful energy spectrum of naturally occurring radiation. In this paper we express the view that different regions of this spectrum are sensitive to variations in lithology. This technique shows that Ratio of two parts of spectrum is depend on average atomic number of the medium. Since the new technology provides us a high quality spectrum, we can use this method to target mineral zones in surrounding rocks as they have higher atomic numbers.